(untitled) (World Bulletin of Social Sciences, 2023)
The article presents information about the use of interactively didactic games in teaching chemistry, the impact of didactic games on the effectiveness of the lesson, and also that didactic games can be used at different stages of the chemistry teaching process based on their description. Examples of didactic games, for example, information about such games as the game "Find the mistake", the game "Fill in the square", the game "Find the mistake", the game "Paint the square", are given in the summary questions. The use of didactic games in chemistry lessons facilitates the study of the subject, makes it interesting and meaningful, ultimately leads to better assimilation of the material, contributes to the formation and development of interest in chemistry.